THE FUNCTION OF WAREHOUSE IN ELEVATED SUPPLY CHAIN: (The case study of farmer’s shallots in East Java) - Hermawan, La Ode Andi; Prasetya, Arik; Worokinasih, Saparila (Accounting Department,, 2021)
Purpose — This research aims to evaluate the function of the warehouse in increasing the supply chain of shallot production in East Java Design/methodology/approach - This research uses explanatory research with a quantitative approach. The object of this research was in four districts of East Java at Nganjuk, Kediri, Malang, and Probolinggo which are the centers of shallot production that have similar environmental conditions. The sampling method in this research used multistage proportional random sampling with 200 respondents as a sample of this research. Data analysis uses the path analysis method by software SEM PLS Software 3.0. Findings - The results show that the warehouse has a significant effect on the integrative supply chain variable, the warehouse has no significant effect on the performance Effort variable and the integrative supply chain has a significant effect on the performance efforts variable.Practical Implications - Supply Chain Improvement is greatly influenced by the warehouse but not by performance Efforts.Originality/value - The key aspect of this research is increasing the effectiveness of warehouse operations in the logistics system and integrated supply chain activities as well as improving the performance of businesses focused on horticulture by approaching farmers and partners (traders). This study expands the literature on the function of warehouse utilization in Supply Chain activities so that it has an impact on improving business performance.Keywords: Warehouse, Supply Chain Integration, Performance Efforts